What historical elements are there in environmental historiography in Latin America? - Gallini, Stefania (Universidad Pedagógica y Tecnológica de Colombia, 2020)
How much has environmental history contributed to the historiography of the region? How much has LatinAmerican environmental historiography contributed to the historiography of the region? Could this relationship be cultivated for the benefit of both? This text addresses the public and talks about history based on a critical reading of Latin American environmental historiography. It suggests that historiography has indicated history the relevance of a wider and more complex historical agency, but it has often been formed by predictable narratives of limited appeal to historians without explicit interests regarding therelationship between societies and ecosystems. It is argued that, when entering the last years of a more mature phase, Latin American environmental historiography has opened a door to better questions concerning fundamental topics of Latin American historiography, questions and objects which seem conceptually, as well as methodologically, innovative. The article presents, by means of examples, topics related with agrarian issues and the construction of the nation state, nonetheless, noting that there is a necessity to better document and systematize the methodology of environmental history. The conclusions move towards the hypothesis that the Anthropocene, as a place of epistemological controversy and methodological challenge, may represent a territory of original contribution by environmental history to Latin American historiography.